Determinants of hepatitis B vaccination status in health care workers of two secondary care hospitals of Sindh, Pakistan: a cross-sectional study - Salman Muhammad Soomar; Amna Rehana Siddiqui; Syed Iqbal Azam; Mairaj Shah (Taylor & Francis Group, 2021)
Background Health care workers (HCWs) are at high risk of Hepatitis B virus (HBV) transmission. Hepatitis B vaccination is effective in protecting against HBV infection. Different factors influence HCW vaccination status such as lack of knowledge & awareness, cost, availability, and hesitancy. This study aimed to determine Hepatitis B vaccination status and factors influencing vaccination status in HCWs of two secondary care hospitals at Sindh, Pakistan. Methods A cross-sectional study was conducted in two secondary care hospitals of Sindh, Pakistan. A total of 252 doctors, nurses, laboratory, and other HCWs were asked about the HBV vaccination coverage using a structured tool. Multivariable ordinal logistic regression was used to determine the association of participant's characteristics, vaccination knowledge with HBV vaccination coverage considering p-value ≤0.05 significant. Odds ratios with 95% confidence interval (CI) were reported. Results Our study found that 64.9% doctors, 75.18% nurses, 58.3% allied HCWs, 40.0% laboratory staff, and 70.8% housekeeping staff were completely vaccinated. HCWs stated job entry requirement as the primary reason for complete vaccination (AOR 4.6, 95% CI 1.5-5.3) from the disease. HCWs working in Aga Khan hospital Karachi and who have received vaccination before working in that hospital had four-time higher odds for hepatitis B vaccination (AOR 4.3, 95% CI 1.7-4.9). Conclusion Two-third of the HCWs were completely vaccinated in secondary care hospitals in Sindh, Pakistan. Hepatitis B vaccination should be made a job entry requirement to achieve more complete vaccination numbers. Vaccination policies require to implement for all part-timers and full-timer health care workers.